PAR: Towards a Reference Architecture for Accessible Platforms in Respiratory Therapies - Marco Santórum; Mayra Carrión-Toro; David Morales-Martínez; Verónica Maldonado-Garcés; Gloria Acosta-Vargas; Patricia Acosta-Vargas (Applied Sciences, 2024)
This article focuses on the Accessible Platform for Respiratory Therapies (PAR), designed according to the iPlus methodology with the application of usability and accessibility criteria, following the guidelines of WCAG 2.1. PAR aims to improve the quality of life for individuals with lung diseases by providing therapeutic education to patients in respiratory recovery. This approach aligns with Sustainable Development Goals 3, 4, and 10 and follows a user-centered design, facilitating access to treatments and techniques to enhance pulmonary function. Additionally, the platform promotes the education and training of professionals in respiratory therapies, reducing disparities in access to healthcare. Sustainability is strengthened by integrating telemedicine technologies, improving efficiency, and reducing costs. Implementing Web Content Accessibility Guidelines (WCAG) 2.1 ensures accessibility and usability for all individuals, including those with disabilities. The combination of WCAG 2.1 and the CSUQ questionnaire not only ensures accessibility but also contributes to sustainability and overall improvement of the user experience, even for individuals with cognitive disabilities.